UJI EFEK EPITELISASI EKSTRAK DAUN EKOR NAGA (Rhaphidophora pinnata (L.f) Schott.) PADA TIKUS - Safriani Rahman; Andi Maulana Kamri (As-Syifaa Jurnal Farmasi, 2019)
Burns are damage to the skin due to contact with sources of heat and radiation. The stage of handling burns involves several phases, namely the inflammatory phase, proliferation and maturation.  This study aims to determine the effect of epithelialization of ethanol extract of dragon tail leaves (Rhaphidophora pinnata (L.f) Schott.) In the process of wound healing. This research was conducted in an experimental laboratory and used rat test animals. 15 animals were divided into 5 groups consisting of group I (control) given Na.CMC, group II were given bioplacenton ointment, group III, IV and V (group given) giving ethanol leaves Rhaphidophora pinnata extract. Giving is done twice a day for 14 days. The wound is made by inducing the back of a mouse with a hot plate of 100o C for 2 seconds.. The results of the study data are the average wound diameter and percent of wound reduction in statistics using oneway ANOVA and LSD follow-up test. Based on the results of the research that has been done, it can be concluded that the ethanol extract of dragon tail leaves  has the effect of epithelialization in rats.